Aedes (Stegomia) albopictus – a dengue threat for southern Australia? - Russell, Richard C; Williams, Craig R; Sutherst, Robert W; Ritchie, Scott A (Communicable Diseases Intelligence, 2005)
Aedes albopictus, the so-called ‘Asian tiger mosquito,' which has invaded areas of the Pacific, the Americas, Africa and Europe, and been intercepted in various Australian seaports in recent years, has now become established on a number of Torres Strait islands in northern Queensland and threatens to invade mainland Australia. As well as being a significant pest with day-biting tendencies, Ae. albopictus is a vector of dengue viruses and is capable of transmitting a number of other arboviruses. The species colonises domestic and peri-domestic containers, and can establish in temperate areas with cold winters. According to predictions made using the CSIRO climate matching software CLIMEX, ® Ae. albopictus could become established elsewhere in Australia, including southern Australia, and lead to these areas becoming receptive to dengue infections—a condition that currently does not exist because the vector Aedes aegypti is confined to Queensland and no species in southern Australia is known to be capable of transmitting dengue. Commun Dis Intell 2005;29:In press.